2002
DOI: 10.1111/j.1745-3984.2002.tb01139.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Computer‐Based Tests on Racial‐Ethnic and Gender Groups

Abstract: In this study data were examined from several national testing programs to determine whether the change from paper‐based administration to computer‐based tests (CBTs) influences group differences in performance. Performances by gender, racial, and ethnic groups on the Graduate Record Examination General Test, Graduate Management Admissions Test, SAT I: Reasoning Test, and Praxis: Professional Assessment for Beginning Teachers, were analyzed to determine whether the shift in testing format from paper‐and‐pencil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 10 publications
1
39
0
2
Order By: Relevance
“…Gallagher, Bridgeman, and Cahalan (2002) examined data from testing programs such as GRE, SAT, Praxis, TOEFL, and GMAT, with regard to gender subgroup. They concluded that females performed better on PPT.…”
Section: Introductionmentioning
confidence: 99%
“…Gallagher, Bridgeman, and Cahalan (2002) examined data from testing programs such as GRE, SAT, Praxis, TOEFL, and GMAT, with regard to gender subgroup. They concluded that females performed better on PPT.…”
Section: Introductionmentioning
confidence: 99%
“…CBT has many advantages over PBT, which include faster score reporting, savings on paper and personnel resources and costs of scoring services (Wise & Plake, 1990), and development of new methods of assessment such as simple adaptations of multiple-choice items to more innovative item types (Jodoin, 2003). Despite these advantages, an important question that arises when tests are administered in both formats is whether or not the scores produced are interchangeable (Wang & Kolen, 2001;Gallagher, Bridgeman, & Cahalan, 2002). For example, scores derived from CBT as compared to PBT might reflect not only the examinee"s proficiency on the construct being measured, but also differences in formatting (including typing vs. hand-writing) and/or computer proficiency.…”
Section: Introductionmentioning
confidence: 99%
“…In their recent study, Terzis and Economides (2011) describe the trends of male and female students towards CBT (21). Yurdabakan (2011) reported that as a result, they highlighted both genders having positive views on CBTs, if they are based on games; they are open and course-related (15).…”
Section: Previous Studiesmentioning
confidence: 99%